GARAGE DOOR CONTROLLER - Irfan Irfan; Jalinas Jalinas, SKom, MM (Jurnal Sistem Komputer, 2001)
Garage door control devices connected using an interface as the means menjabatani to pass or transfer data from the microcomputer to the periphery and vice versa. Computer as the controlling and processing the data or information into and out to the periphery of the data previously received by the interface.Â  Which is an electromechanical steppe r motor that works by changing the electronic pulses into discrete mechanical movements, movements of the stepper motor can be arranged ie clockwise or counterclockwise dandapat applied to various kinds perngkat or peripherals such as disk drives, hard dis k cutter.